Improvement of CO2 purifying system by photocatalyst for application in microalgae culture technology - Oanh, Doan Thi; Yen, Quach Thi Hoang; Toan, Nguyen Thi; Trung, Nguyen Quoc; Chi, Tran Que; Chuyen, Nguyen Hong; Nguyet, Tran Thi Minh; Kim Anh, Bui Thi; Kim, Dang Dinh (Vietnam Journal of Science and Technology, 2016)
By reactive grinding method Vanadium-doped rutile TiO2 nanoparticle material was obtained with an average particle size of 20‐40nm, the Brunauer–Emmet–Teller (BET) specific surface area about 20 m2g−1 and it absorbed strongly in the UV region and increased at the visible wavelength of 430 – 570 nm. This study focused on the improvement of exhaust gas treatment from coal-fired flue gas of the traditional adsorption-catalysis system (Modular System for Treating Flue Gas - MSTFG) by using the V2O5/TiO2 Rutile as photocatalyst. The results showed that integrating both catalytic systems mentioned above increased the gas treatment efficiency: CO from 77 % to over 98 %, NOx from 50 % to 93 %, SO2 was absent as opposed to the input gas component. Also it showed that V2O5/TiO2 Rutile integrated with MSTFG has got high efficiency of CO treatment, also secured the high obtained CO2 concentration as a valuable carbon source for microagal mass culture as well as saving energy and simplifying devices.